Under Bech's eyes: emotional geographies of the European East in John Updike's short stories. - Bryla, Martyna Marika (Universidad de Sevilla, 2018)
John Updike’s short stories about Henry Bech’s diplomatic adventures in the European East have been analysed mainly in the context of the Cold-War balance of power and Updike’s ambivalent attitude to communist Russia. While the hard-boiled politics constitute the backdrop of Bech’s cultural mission, the three stories which I discuss in this essay entertain tensions between the official and the personal, which in turn shape the protagonist’s representations of Eastern European others. Accordingly, by combining imagology with elements of geocriticism and affect studies, this essay explores how cultural patterns of perceiving alterity are intertwined with emotions to produce Bech’s emotional geographies of the European East, which in mapping the other reflect back on and consolidate Bech’s American self.
https://revistascientificas.us.es/index.php/ESTUDIOS_NORTEAMERICANOS/about
Keywords: Updike, John (1932-2009) - Crítica e interpretación; Literatura - Historia y crítica; John Updike; Henry Bech; Eastern Europe; Soviet Union; Cold War; Imagology; Affect; Emotional geographies; Imaginative geographies